Trend Riset Isu Sosiosaintifik Berbasis Database Jurnal Scopus: Studi Bibliometrik 2011-2021 - Yokhebed; sutarno, Sutarno; Masykuri, Mohammad; Prayitno, Baskoro Adi (Postgraduate, University of Mataram, 2023)
The implementation of socioscientific issues in science learning has increased recently. The purpose of this study is to highlight research trends over the previous ten years by examining the findings of bibliometric papers on socio-scientific issues. A total of 648 articles from the English-language Scopus database were analyzed using the VOS Viewer. The results of the analysis reveal that studies related to socio-scientific issues over the last ten years are still an increasing research trend. Keywords related to socio-scientific issues such as argumentation, decision making, scientific literacy, critical thinking, and climate change. The journal sources that were most cited were the international journal of science education, journal of research in science teaching, research in science education, international journal of science and mathematics education, science and education. Articles that are widely cited by other authors are Sadler T.D, Zeidler, D.L, Osborn, J, Eilks, I, Erduran, S, Lederman, N.G, Simon, S. Leading countries in the field of socio-scientific issues are the United States, Germany, Sweden, Taiwan, Australia, Turkey, United Kingdom, Canada, Spain, Indonesia. Further researchers can conduct scientific studies on socio-scientific issues by using educational technology in the form of digital media and other variables that have not been studied or are still little researched.